Assessing the Evidence for Asymmetrical Switch Costs and Reversed Language Dominance Effects – A Meta-Analysis. Issue 1 (13th September 2021) - Gade, Miriam; Declerck, Mathieu; Philipp, Andrea M.; Rey-Mermet, Alodie; Koch, Iring
Two seemingly counterintuitive phenomena – asymmetrical language switch costs and the reversed language dominance effect – prove to be particularly controversial in the literature on language control. Asymmetrical language switch costs refer to the larger costs for switching into the dominant language compared to switching into the less dominant language, both relative to staying in either one language. The reversed language dominance effect refers to longer reaction times when in the more dominant of the two languages in situations that require frequent language switching (i.e., mixed-language blocks). The asymmetrical language switch costs are commonly taken as an index for processes of transient, reactive inhibitory language control, whereas the reversed language dominance effect is taken as an index for sustained, proactive inhibitory language control. In the present meta-analysis, we set out to establish the empirical evidence for these two phenomena using a Bayesian linear mixed effects modelling approach. Despite the observation of both phenomena in some studies, our results suggest that overall, there is little evidence for the generality and robustness of these two effects, and this holds true even when conditions – such as language proficiency and preparation time manipulations – were included as moderators of these phenomena. We conclude that asymmetrical switch costs and the reversed language dominance effect are important for theory development, but their utility for theory testing is limited due to their lack of robustness and the absence of confirmed moderatory variables.